Food security in a food abundant world an individual country perspective - Schmitz, Andrew; Kennedy, P. Lynn.; Schmitz, Troy Gordon (Bingley, U.K. : Emerald, 2016)
Food insecurity can result from various events. When food is abundant, the entitlement to food is limited by endowments, the ability to trade, and potential transfers from family or the government. This volume utilizes a country and regional perspective to examine food insecurity. We consider the interaction between income and the share of household expenditures on food. The epidemiological risk assessment approach to food security issues is utilized as a function of agricultural and production, food distribution, and health policies. The interdependence of food security and climate change is examined. Overall trends in economic growth and poverty reduction, constraints and bottlenecks in agricultural productivity growth, regional trade agreements, and other influential policies are reviewed and discussed. We also consider food security as related to food consumption patterns and obesity. The role of income diversification as well as the impact of Farmer School Fields on food security are examined. The impact of inheritance and transfer entitlements is examined as we consider the role of remittances as well as 'ganyu' or casual labor in determining food security.
Food security and the role of food storage / Andrew Schmitz, P. Lynn Kennedy -- Food security, subsistence agriculture, and Working's model / Charles B. Moss, James F. Oehmke, Alexandre Lyambabaje -- A probabilistic approach to food security / David Zilberman, Yanhong Jin -- The high value to society of modern agriculture : global food security, climate protection, and preservation of the environment evidence from the European Union / Harald von Witzke, Steffen Noleppa -- Off-farm labor allocation, income, and food consumption among rural farm households in transitional Albania / Ayuba Seidu, Gulcan Onel -- The status and challenges of food security in Europe and Central Asia / Kateryna G. Schroeder, William H. Meyers -- Factors affecting adolescent obesity in urban China / Carl Anfinson ... [et al.] -- Sugar, fat, or protein : are all food insecure households eating the same? The case of small rice producers in Peru / Pilar Useche, Jennifer Twyman -- Food safety and food security in the Canamex trade corridor / Eric P. Thor, Octavio Valdez Lafarga -- Impact of remittance on food security in Bangladesh / Madhav Regmi, Krishna P. Paudel -- Informal "Ganyu" labor supply, and food security : the case of Malawi / Isaac Sitienei, Ashok K. Mishra, Aditya R. Khanal -- The political economy of export restrictions : the case of Vietnam and India / Kathy Baylis, Murray E. Fulton, Travis Reynolds -- Food security policy at the extreme of the water-energy-food nexus : the kingdom of Saudi Arabia / Hannah Pieters, Johan Swinnen -- The role of nudges in reducing food waste / David R. Just, Jeffrey M. Swigert -- Wastage in food value chains in developing countries : evidence from the potato in Asia / Bart Minten ... [et al.].
Print version record
Keywords: Business & Economics -- Development -- Economic Development; Business & Economics -- Development -- Sustainable Development; Development economics; Food security; Food security -- Economic aspects; Nutrition policy